Randomized Phase IIB Evaluation of Weekly Paclitaxel versus Weekly Paclitaxel with Oncolytic Reovirus (Reolysin®) in Recurrent Ovarian, Tubal, or Peritoneal Cancer: an NRG Oncology/Gynecologic Oncology Group Study - Cohn, David E. (Gynecol Oncol, 2017)
OBJECTIVE: To assess whether the addition of oncolytic reovirus (Reolysin®) to weekly paclitaxel prolonged progression-free survival (PFS) in the treatment of women with recurrent or persistent ovarian, tubal or primary peritoneal cancer. PATIENTS AND METHODS: Patients with recurrent or persistent epithelial ovarian, tubal, or peritoneal carcinoma, measurable or detectable disease, and three or fewer prior regimens were randomly assigned to paclitaxel (80 mg/m(2) intravenously days 1, 8, and 15 every 4 weeks) or the combination of paclitaxel (80 mg/m(2) intravenously days 1, 8, and 15) plus reovirus 3×10(10) TCID(50)/day intravenously on days 1-5, both every 4 weeks until disease progression or toxicity. The primary end point was PFS. The study was designed with 80% power for a one-sided alternative at a 10% level of significance to detect a reduction in the hazard by 37.5%. RESULTS: The study accrued 108 patients, 100 of whom were evaluable for toxicity. Median PFS was 4.3 months for paclitaxel and 4.4 months for paclitaxel plus reovirus (hazard ratio, 1.11; 90% two-sided CI, 0.78 to 1.59; one-sided P = 0.687). The proportion responding (overall response rate) to paclitaxel was 20% among 45 patients with measurable disease receiving paclitaxel alone, and 17.4% among the 46 patients treated with the combination. The asymptotic relative probability of responding was 0.87 (90% CI, 0.42 to 1.79). Severe adverse events were more common in the combination regimen than in paclitaxel arm for severe neutropenia (grade ≥ 4, 12% versus 0%), and severe respiratory adverse events (grade ≥ 3, 25% versus 2%). No deaths were considered treatment related. CONCLUSION: The addition of reovirus to weekly paclitaxel in the treatment of women with recurrent or persistent ovarian, tubal or peritoneal cancer did not sufficiently reduce the hazard of progression or death to warrant further investigation.